The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s40279-018-1003-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Intervention on Cardiac Function in Type 2 Diabetes Mellitus: A Systematic Review

Abstract: In this systematic literature review, exercise intervention is shown to improve diastolic function and counteract adverse remodeling leading to cardiac dysfunction in animals and humans with Type 2 Diabetes Mellitus (T2DM) or diabetic cardiomyopathy. Given the therapeutic effects of exercise intervention on cardiac function and structure, it should be a cornerstone in the treatment of T2DM patients not only to improve glycemic control but also to specifically enhance cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Several studies have assessed the effects of various exercise interventions on diastolic function in people with T2D, predominantly using echocardiography (10). In general, these have shown that exercise training has favourable effects on diastolic function, although with inconsistent results, likely due to differences in study populations, modes of exercise intervention, and various measures of diastolic function being employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have assessed the effects of various exercise interventions on diastolic function in people with T2D, predominantly using echocardiography (10). In general, these have shown that exercise training has favourable effects on diastolic function, although with inconsistent results, likely due to differences in study populations, modes of exercise intervention, and various measures of diastolic function being employed.…”
Section: Discussionmentioning
confidence: 99%
“…Whether weight loss or exercise training can improve subclinical cardiac dysfunction in people with T2D remains to be established. There have been no randomized controlled trials assessing cardiac function with a MRP and the results of trials in exercise training have been inconsistent (10).…”
Section: Abbreviationsmentioning
confidence: 99%
“…The mechanism looks to be more bidirectional, synergistic on the origin, and of dose-response character. [65] There is accumulated evidence on the improvement in ED due to cardiovascular, neurological, metabolic, and other associated factors. It is a synergistic and dose-effect role of the PE on the ED, particularly in young and early elderly age group.…”
Section: Mechanism Of Physical Exercise Effect On Erectile Dysfunctionmentioning
confidence: 99%
“…If biomarkers or non-invasive imaging modalities could be used for early identification of high-risk patients [46,140], it would be feasible to prescribe personalized exercise programs based on risk stratification. Since exercise may not only mitigate cardiac dysfunction but also improve the outcome of T2DM [36,134,[141][142][143], a therapeutic approach with a tailored exercise prescription would positively impact DCM management in the future. To this end, the development of tools for early diagnosis and optimization of risk stratification models would be pivotal and in conjunction with well-designed clinical trials could provide the evidence to facilitate timely implementation.…”
Section: Exercise Is An Early Diagnostic Tool For Prevention and Bettmentioning
confidence: 99%